Sistem Informasi Akademik Berbasis Website untuk Meningkatkan Prestasi Belajar Siswa MAN 3 Cirebon di Masa Pandemi Covid-19 - Nanda Septian; Nana Suarna; Dita Rizki Amalia (INTERNAL (Information System Journal), 2022)
Parents need information about children's activities and learning outcomes in school. Academic information system is one way that information about the results of learning activities can be delivered more easily and quickly by the school and can be well received by parents as guardians of students. Therefore, an academic information system is designed that is able to provide information about student learning outcomes and activities so that parents can still supervise learning activities in schools. The system is expected to be able to be a material for evaluating children on the results of their learning in school so that children are able to become outstanding students. The purpose of this study is so that parents can find out the results of children's learning, namely grades and other learning activities in school. This research uses a qualitative approach where data collection is obtained from interviews, observations, and documentation. In addition, this system is designed using the waterfall method with stages of analysis, design or design, implementation, verification, and maintenance. The result of the research is the application of a web-based academic information system capable of being a means of parental supervision of the results of children's learning activities so that it has an impact on increasing student achievement.